38 Adapting an Emergency General Surgery Service in Response to the COVID-19 Pandemic. (4th May 2021) - Hickland, P; Clements, J; Convie, L; McKay, D; McElvanna, K
Abstract: Introduction: In response to the COVID-19 pandemic, our emergency general surgery (EGS) service established an enhanced ambulatory service and undertook non-operative management of selected pathologies. This study compares the activity of our service before and after these changes. Method: Patients referred by the emergency department were prospectively identified over a four-week period beginning from the date of reconfiguration (COVID) and compared to patients retrospectively identified from the same period the previous year (Pre-COVID) and followed up for 30 days. Data was extracted from handover documents and electronic care records. Results: There were 281 and 283 patients during the Pre-COVID and COVID periods, respectively. Rates of admission decreased (78.1% to 41.7%) whilst there were increased rates of ambulation (7.1% to 17.3%) and discharge (6% to 22.6%). Duration of admission decreased (6.9 to 4.8 days), and there were fewer operative and endoscopic interventions (78 to 40). There were increased ambulatory investigations (11 to 39), telephone reviews (0 to 39), and use of early CT to facilitate discharge (5% to 34.7%). There were no differences in 30-day readmission or mortality in any group. Conclusions: Restructuring of our EGS service in response to COVID-19 facilitated an increased use of ambulatory services and imaging, whilst maintaining patient safety.